Effect of the novel anti-NGF monoclonal antibody DS002 on the metabolomics of pain mediators, cartilage and bone - Jin, Dandan; Yang, Haoyi; Chen, Zhiyou; Hong, Yuxin; Ma, Hehua; Xu, Zhenzhen; Cao, Bei; Fei, Fei; Zhang, Yuwen; Wu, Weitao; Tang, Lei; Sun, Runbin; et al. (Frontiers in Pharmacology, 2024)
The anti-nerve growth factor antibody class of drugs interrupts signaling by blocking NGF binding to TrkA receptors for the treatment of pain; however, this target class of drugs has been associated with serious adverse effects in the joints during clinical trials. DS002 is a novel anti-nerve growth factor antibody drug independently developed by Guangdong Dashi Pharmaceuticals. The main purpose of this study is to explore the correlation between DS002 and pain as well as cartilage and bone metabolism with the help of metabolomics technology and the principle of enzyme-linked reaction, and to examine whether DS002 will produce serious adverse effects in joints caused by its same target class of drugs, in order to provide more scientific basis for the safety and efficacy of DS002. Our results showed that DS002 mainly affected the metabolism of aromatic amino acids and other metabolites, of which six metabolites, l -phenylalanine, 5-hydroxytryptophan, 5-hydroxytryptophan, 3-indolepropionic acid, kynurenine, and kynurenine, were significantly altered, which may be related to the effectiveness of DS002 in treating pain. In addition, there were no significant changes in biological indicators related to cartilage and bone metabolism in vivo, suggesting that DS002 would not have a significant effect on cartilage and bone metabolism, so we hypothesize that DS002 may not produce the serious adverse effects in joints caused by its fellow target analogs. Therefore, the Anti-NGF analgesic drug DS002 has the potential to become a promising drug in the field of analgesia, providing pain patients with an efficient treatment option without adverse effects..